Textile Wastewater Treatment by Mutant Enterobacter sp. - Sangkharak, Assoc. Prof. Dr. Kanokphorn (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
The current study aimed to enhance the ability of Enterobacter to decolorize textile wastewater (TW) by sequential mutation using the UV irradiation method. The wild type was exposed to UV for 60 sec at a distance of 60 cm. The mutant strain showed the highest decolorization efficiency at 87.52±0.11% after using the UV irradiation for 60 sec. While, only 81.15% was observed by wild type. Afterward, the effects of environmental conditions were optimized to enhance the decolorization of TW. The mutant strain showed the highest decolorization efficiency at 90.88% using 100% of TW under pH 7, 100 rpm, 35 °C and 12 h of incubation. Moreover, mutant not only decolorize dye in TW but also improved the quality of the water under optimal conditions. The treated TW met the criteria of the Water Quality Standard, Thailand.